State Type and Congressional Voting on the Minimum Wage - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1998)
How members of Congress vote on increases in the minimum wage is a function of several factors, most notably party affiliation and constituent interest. But also among those factors is the existence of "right-to-work" laws in the representative's state and the presence of labor unions, especially as they represent a voting constituency. This paper examines congressional voting patterns on the minimum wage from 1949, when the first vote to increase the wage occurred, to 1996, when the last vote occurred, and finds a relationship between union strength and positive voting, a relationship between "right-to-work" states and negative voting, and a decline in the significance of unions as a factor affecting congressional voting as unionism has declined.
Keywords: 330